Improving the Capacity of Rice Farmers Through Micro-Business Management and Information Technology Training in Pematang Johar Village - Elisabeth Nainggolan; Joni Joni; Widalicin Januarty; Najla Najla; Loo Teck Khun; Phan Bao Giang; Annisa I. Hafifa Siregar (Eastasouth Journal of Effective Community Services, 2025)
This community service activity aims to improve the capacity of rice farmers in Pematang Johar Village through micro-business management training and the use of information technology in agricultural activities. Farmers' low business management skills and limited access to agricultural information are major obstacles to increasing productivity and income. The activity was implemented through socialization, training, mentoring, and evaluation. The results showed an increase in farmers' understanding of farm management, simple financial record keeping, and the ability to use Android-based agricultural applications. This activity encourages farmers to manage their farms more efficiently, transparently, and sustainably.